1998
DOI: 10.1089/cbr.1998.13.239
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose, Fractionated Radioimmunotherapy for B-cell Malignancies using131I-LYM-1 Antibody

Abstract: Although advanced disease often interrupted therapy prematurely, the results from 131I-Lym-1 therapy are clearly promising and warrant additional trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 21 publications
3
59
0
1
Order By: Relevance
“…The antibody recognizes a 31-to 35-kDa antigen presumed to be a polymorphic variant of the HLA-DR antigen, and thought to have a specific avidity for malignant B cells. [6][7][8] Although responses were reported in patients with NHL and chronic lymphocytic leukemia (CLL), the criteria for response were not standard making the data difficult to interpret. 9 Other investigators have reported on 131 I-labeled OKB7, a murine IgG2b, 10 and iodine I 131 LL2 (anti-CD22), 11 among other RICs.…”
Section: Early Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibody recognizes a 31-to 35-kDa antigen presumed to be a polymorphic variant of the HLA-DR antigen, and thought to have a specific avidity for malignant B cells. [6][7][8] Although responses were reported in patients with NHL and chronic lymphocytic leukemia (CLL), the criteria for response were not standard making the data difficult to interpret. 9 Other investigators have reported on 131 I-labeled OKB7, a murine IgG2b, 10 and iodine I 131 LL2 (anti-CD22), 11 among other RICs.…”
Section: Early Studiesmentioning
confidence: 99%
“…[6][7][8] Although responses were reported in patients with NHL and chronic lymphocytic leukemia (CLL), the criteria for response were not standard making the data difficult to interpret. 9 Other investigators have reported on 131 I-labeled OKB7, a murine IgG2b, 10 and iodine I 131 LL2 (anti-CD22), 11 among other RICs. Activity was noted in preliminary trials in which 90 Y was conjugated with anti-idiotype antibodies; however, this approach was not considered practical.…”
Section: Early Studiesmentioning
confidence: 99%
“…It binds to cells that express the CD22 antigen on their surface and kills the cells by high-energy β − radiation from the 90 Y. Lymphocide ® is currently being tested in Phase III clinical trials in the treatment of lymphoma, leukaemia, and some immune diseases (e.g., lupus). The Phase I/II clinical trial results showed that Lymphocide ® has a good safety profile (mostly grade 1 toxicity) and exerts anti-tumour activity in aggressive DeNardo et al (1998) found that 52% of patients that had failed conventional chemotherapy achieved partial or complete remission after receiving the treatment with Oncolym ® . A possible side effect of Oncolym ® is reduction of blood cell counts; however, this is usually reversible after the treatment.…”
Section: ® )mentioning
confidence: 99%
“…14 Furthermore, theoretical and practical considerations for fractionated RIT were addressed in these very important studies at the University of California in Davis. [15][16][17][18] Other studies explored targeting CD37 using an iodine-131 loaded antibody; 19 although responses were seen in small number of patients, the target was not specific for Bcells and considerable toxicity was noted. CD22 was targeted by the monoclonal antibody LL2 conjugated to 90 Y, which is also available in a humanized form (hLL2).…”
Section: Selection Of Targets For Rit Historical Developmentmentioning
confidence: 99%